Bone mineral density in patients with predialysis chronic kidney disease. (September 2013) - Aggarwal, H. K.; Jain, Deepak; Yadav, Sachin; Kaverappa, Vipin
Abstract Background: There is limited data available especially in Indian Population about prevalence of reduced bone mineral density (BMD) and various factors associated with it in CKD patients not on dialysis. Material: This study included 75 adult patients. Patients were divided into three groups depending upon GFR. Serum creatinine, albumin, calcium, phosphate (PO4), alkaline phosphatase, iPTH and Vitamin D were measured at baseline. BMD was measured by dual energy X-ray absorptiometry. Results: There were 51 male and 24 female patients. The mean serum phosphate, alkaline phosphatase and iPTH levels increased steadily as CKD progressed. On the other hand, mean corrected serum calcium and Vitamin D levels decreased progressively in group A, B and C. The mean serum PTH values in group A, B and C were 137.16 ± 109.85, 265.02 ± 132.03 and 328.14 ± 119.23 pg/mL, respectively and there was significant increase in mean PTH level from group A to group C (p < 0.05). The mean level of vitamin D showed a trend of declination from group A to C (p < 0.05). Z-score for group A, group B and group C was 1.11 ± 2.39, 0.87 ± 2.66 and −0.92 ± 1.59, respectively. Similarly, T score for the three groups were 0.47 ± 2.34, −0.4 ± 2.00 and −1.524 ± 1.42. Both T-score and Z-score positively correlated with GFR. There was negative correlation between Z-score and iPTH, and positive correlation with Vitamin D. Conclusion: Reduced bone density was seen early in the course of CKD as estimated from reduced BMD levels, increased prevalence of osteoporosis and increased fracture risk and it worsened with the progression of CKD.